Dose of antivenom for the treatment of snakebite with neurotoxic envenoming: Evidence from a randomised controlled trial in Nepal - Alirol, E; Sharma, S; Ghimire, A; Poncet, A; Combescure, C; Thapa, C; Paudel, V; Adhikary, K; Taylor, W; Warrell, D; Kuch, U; Chappuis, F (Public Library of Science, 2017)
Currently, there is inadequate evidence on which to base clinical management of neurotoxic snakebite envenoming, especially in the choice of initial antivenom dosage. This randomised controlled trial compared the effectiveness and safety of high versus low initial antivenom dosage in victims of neurotoxic envenoming.This was a balanced, randomised, double-blind trial that was conducted in three health care centers located in the Terai plains of Nepal. Participants received either low (two vials) or high (10 vials) initial dosage of Indian polyvalent antivenom. The primary composite outcome consisted of death, the need for assisted ventilation and worsening/recurrence of neurotoxicity. Hourly evaluations followed antivenom treatment. Between April 2011 and October 2012, 157 snakebite victims were enrolled, of which 154 were analysed (76 in the low and 78 in the high initial dose group). Sixty-seven (43·5%) participants met the primary outcome definition. The proportions were similar in the low (37 or 48.7%) vs. high (30 or 38.5%) initial dose group (difference = 10·2%, 95%CI [-6·7 to 27·1], p = 0·264). The mean number of vials used was similar between treatment groups. Overall, patients bitten by kraits did worse than those bitten by cobras. The occurrence of treatment-related adverse events did not differ among treatment groups. A total of 19 serious adverse events occurred, including seven attributed to antivenom.This first robust trial investigating antivenom dosage for neurotoxic snakebite envenoming shows that the antivenom currently used in Nepal performs poorly. Although the high initial dose regimen is not more effective than the low initial dose, it offers the practical advantage of being a single dose, while not incurring higher consumption or enhanced risk of adverse reaction. The development of new and more effective antivenoms that better target the species responsible for bites in the region will help improve future patients' outcomes.The study was registered on clinicaltrials.gov (NCT01284855) (GJ 5/1).